Classification of large seismic events at Lucky Friday mine - W. P. Blake; J. K. Whyatt; T. J. Williams (The Institute of Materials, Minerals and Mining, 1905)
A study at the Idaho mine revealed that, despite the apparent randomness of seismic events, common characteristics defined five recurring types. These characteristics included the geological structure that slipped, the first-motion pattern and the location and intensity of damage. Many large events caused little or no damage, and where it did occur it was concentrated at intersections between slipping structures and mine openings. Of 39 events between 1989 and 1994 with local magnitudes of 2.5 or more, 10 were caused by slip on bedding planes in the southern limb of the mine, 6 occurred near the vein along a set of near-vertical faults that form the central shear zone, 8 were strike-slip events on the Southern Control Fault, 4 were by slip on the vein itself and 10 involved strike-slip and/or dip-slip movement along the North Control Fault. Strategies for control of mining-induced seismicity need to consider all five types of event, lest a strategy to reduce one type increases others